2000
DOI: 10.1046/j.1365-2893.2000.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Infections with hepatitis B and C viruses in patients on maintenance dialysis in Romania and in former communist countries: yellow spots on a blank map?

Abstract: We studied prospectively, between 1993 and 1998, the prevalence and incidence of markers against hepatitis B virus (HBV), hepatitis C virus (HCV) and hepatitis D virus (HDV), in 180 patients with chronic renal failure, dialysed in the Nephrological Clinic, Cluj. HBV and HCV markers were common in the patients who were already on haemodialysis in 1993 (antibodies to hepatitis B core antigen [HBcAb]: 57.9-88%; hepatitis B surface antigen [HBsAg]: 8.7-25%; antibodies to HCV [anti-HCV]: 73.7-100%; simultaneous occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
50
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 17 publications
10
50
2
Order By: Relevance
“…Regarding HCV infection in hemodialysis patients, studies showed rates ranging from 3.4%, in the Netherlands (Schneeberger et al 2000), to more than 70%, in Eastern Europe (Vladutiu et al 2000). In our country, HCV prevalence rates of 20.3%, 23.8%, 33.4% and 39% were recently found in Santa Catarina (Moraes 2001), Bahia (Santana et al 2001), Minas Gerais (Busek et al 2002), and Goiás (Carneiro et al 2001), respectively.…”
supporting
confidence: 45%
See 1 more Smart Citation
“…Regarding HCV infection in hemodialysis patients, studies showed rates ranging from 3.4%, in the Netherlands (Schneeberger et al 2000), to more than 70%, in Eastern Europe (Vladutiu et al 2000). In our country, HCV prevalence rates of 20.3%, 23.8%, 33.4% and 39% were recently found in Santa Catarina (Moraes 2001), Bahia (Santana et al 2001), Minas Gerais (Busek et al 2002), and Goiás (Carneiro et al 2001), respectively.…”
supporting
confidence: 45%
“…Since both viruses are efficiently transmitted by parenteral route, patients undergoing hemodialysis are at high risk of acquiring these bloodborne hepatitis agents (Cañero-Velasco et al 1998, Covic et al 1999, Vladutiu et al 2000. In addition, infected patients have an increased tendency to develop chronic hepatitis and also to be a potential reservoir for its transmission (Goldbloom & Reed 1980, Harnett et al 1988.…”
mentioning
confidence: 99%
“…In some countries, this infection has been controlled in dialysis centers by adherence to hemodialysis-specific infection-control practices and to hepatitis B vaccination (Ambuhl et al 2000, Finelli et al 2005. However, for others, HBV infection is still an important problem to patients (Vladutiu et al 2000, Otedo et al 2003, Kumar et al 2005. Nevertheless, HBV infection outbreaks are still seen when failures in infection control procedures occur (De Castro et al 2000, Lewis-Ximenez et al 2001.…”
mentioning
confidence: 99%
“…These data show that HBV infection continues to be an important problem in Brazilian dialysis units. Blood transfusion has been pointed as an important risk factor for hepatitis B in hemodialysis population (Vladutiu et al 2000, Otedo et al 2003. In the present investigation, patients who received blood transfusion before 1993 had a 2.3-fold (95% CI: 1.6.-3.3) greater risk of HBV positivity compared to those that were transfused after.…”
mentioning
confidence: 99%
See 1 more Smart Citation